2019
DOI: 10.1302/0301-620x.101b9.bjj-2018-1369.r1
|View full text |Cite
|
Sign up to set email alerts
|

Cemented humeral stemversuspress-fit humeral stem in total shoulder arthroplasty

Abstract: Aims The aim of this study was to evaluate the differences in revision and complication rates, functional outcomes, and radiological outcomes between cemented and press-fit humeral stems in primary anatomical total shoulder arthroplasty (TSA). Materials and Methods A comprehensive systematic review and meta-analysis was conducted searching for studies that included patients who underwent primary anatomical TSA for primary osteoarthritis or rheumatoid arthritis. Results There was a total of 36 studies with 927 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…While studies have evaluated the differences between cemented and press-fit humeral stems at short-term (>2 years of follow-up) and mid-term time points (>5 years of follow-up) [ 2 , 16 ], this is one of the first studies to report on long-term patient reported outcomes comparing cemented and press-fit humeral stems. In our study, we found that both cemented and press-fit humeral stems provide sustained and significant improvements in terms of shoulder function and pain.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have evaluated the differences between cemented and press-fit humeral stems at short-term (>2 years of follow-up) and mid-term time points (>5 years of follow-up) [ 2 , 16 ], this is one of the first studies to report on long-term patient reported outcomes comparing cemented and press-fit humeral stems. In our study, we found that both cemented and press-fit humeral stems provide sustained and significant improvements in terms of shoulder function and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews summarized the results for various implant types: Uy et al reported on stemmed cemented TSA (pooled mean FE: 132°, ER: 37°) vs. pressfit implants (pooled mean FE: 146°, ER: 53°). 27 Liu et al compared stemless TSA vs. stemmed TSA and reported similar postoperative functional outcomes and complication rates as well as a shorter operative time and decreased intraoperative blood loss for stemless implants. 17 The weighted mean postoperative flexion for stemless implants was 142°, and 47° on ER.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we started contemplating a definitive treatment by performing a ORIF with bone graft or a shoulder arthroplasty, but at that moment, the patient was lost at follow-up. Given the poor bone quality, after the removal of the EF, we would probably have implanted a hemiarthroplasty or a reverse prosthesis with a press-fit primary humeral stem fixation, considered an optimal choice because of the possible easier revision, decreased operative time, healing time, and resolution of the symptoms [16]. After 7 months, the patient came back to our department, suffering from pain and severe functional limitation, compounded by a preternatural movement of the joint.…”
Section: Discussionmentioning
confidence: 99%